28. The Potential of Red Watermelon Extract (Citrullus vulgaris) to Decrease Blood Glucose Levels in Mice (Mus musculus) Were Exposed with Cigarette Smoke - Irfani Rahmi; Roslizawaty Roslizawaty; Azhar Azhar; Razali Daud; Syafruddin Syafruddin; Ismail Ismail (Jurnal Medika Veterinaria, 2019)
The aim of this research was to find out the potential of red watermelon extract (Citrullus vulgaris) to lower the high blood glucose levels in mice (Mus musculus) as a result of exposure to cigarette smoke. sample was 15 mice  which are divided into 3 treatment groups, each group consists of 5 mice. Positive group as (KP) is the treated group with one cigarette exposure per day. Treatment group 1 as (K1) is the treated group with exposure to one cigarette and 22 mg dose extract of red watermelon of each mice per day. Then the treatment group 2 as (K2) is the group that was given exposure to one cigarette and 44 mg dose extract of red watermelon of each mice per day. Blood glucose testing on mice was conducted on days 0, 15, and  30 after giving the exposure of cigarette smoke and extract of red watermelon. The result showed that (KP) has significant different with (K1) and (K2) (P0.05), meanwhile (K1) and (K2) was not significant different (P0.05). The results also showed H-0 was significantly different from the H-15 and H-30 (P 0.05), while the H-15 and H-30 was not significantly different (P 0.05). From the results, it can be concluded that 22 mg and 44 mg of red watermelon extract are not able to lower the high blood glucose levels on mice which were exposed to cigarette smoke..